Do we need internal medicine specialists in physical therapy? Recognizing the need for updating the clinical practice paradigm - Alotaibi, Mansour M. (Frontiers in Rehabilitation Sciences, 2025)
The growing demand for healthcare services and development of healthcare present an opportunity for expanding physical therapy roles into internal medicine. This perspective discusses the potential benefits and limitations of establishing a formal internal medicine specialization for physical therapists (PTs). While PTs already contribute significantly to chronic disease prevention and treatment, their current scope of practice lacks structured training in internal medicine domains such as metabolic, autoimmune, renal, and systemic inflammatory disorders. Integrating internal medicine into PT education and clinical practice could enhance early identification of red flags, embrace interdisciplinary collaboration, and improve non-pharmacological interventions for various internal medicine-related diseases. Nevertheless, this expansion must be approached with caution, ensuring clear scope definitions, adequate training, and collaborative implementation to mitigate risks such as role ambiguity or misdiagnosis. Drawing on global experiences from advanced practice models and emerging literature, this paper calls for a discussion on the feasibility, safety, and value of internal medicine specialization in physical therapy practice. The goal of this perspective is not to replace medical professionals but to augment chronic disease management through targeted evidence-based rehabilitation strategies and preventative approaches.